2021
DOI: 10.1088/2053-1591/abf475
|View full text |Cite
|
Sign up to set email alerts
|

A stretchable superhydrophobic coating with electrothermal ability for anti-icing application

Abstract: Surface icing in the transmission lines may cause serious accidents. Although the superhydrophobic/electrothermal synergistically anti-icing strategy has been introduced, most coatings tended to lose superhydrophobicity under large deformation. In this research, we prepared a kind of stretchable superhydrophobic coating by partially embedding the modified graphene into the Ecoflex elastomer. The excellent resilience of the Ecoflex elastomer together with the outstanding interficial area of graphene results in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 31 publications
0
11
0
Order By: Relevance
“…[83] They found that the heat generated by the biomimetic superhydrophobic CNW/ PDMS nanocomposite film is faster than that of the refrigeration speed of the low-temperature platform at 40 V, and the superhydrophobic CNW/PDMS nanocomposite can melt a 8 mm thick ice layer within 150 s under a working voltage of 40 V. [83] Peng et al prepared a stretchable superhydrophobic coating (i.e., maintain superhydrophobicity under 300% strain) by embedding modified graphene into the Ecoflex elastomer to achieve the electrothermal ability for anti-icing application. [93] A water droplet (5 µL at −15 °C) on this graphene-based superhydrophobic coating was completely frozen after 394 s, while this superhydrophobic coating can melt a 2 mm thick ice layer within 115 s under a voltage of 20 V. [93] Wang et al showed that superhydrophobic graphene composite can suppress ice nucleation of a water droplet (5 µL at −15 °C) for 335 s, and this superhydrophobic composite can melt an ice layer (≈3 mm) in 70 s under a voltage of 50 V because of the synergistic effect of surface superhydrophobicity and electro-thermal property. [91] Zhang et al designed a thermo-mechanical anti-icing/de-icing ) adapted with permission.…”
Section: Electro-thermal Promoted Aimmentioning
confidence: 99%
See 1 more Smart Citation
“…[83] They found that the heat generated by the biomimetic superhydrophobic CNW/ PDMS nanocomposite film is faster than that of the refrigeration speed of the low-temperature platform at 40 V, and the superhydrophobic CNW/PDMS nanocomposite can melt a 8 mm thick ice layer within 150 s under a working voltage of 40 V. [83] Peng et al prepared a stretchable superhydrophobic coating (i.e., maintain superhydrophobicity under 300% strain) by embedding modified graphene into the Ecoflex elastomer to achieve the electrothermal ability for anti-icing application. [93] A water droplet (5 µL at −15 °C) on this graphene-based superhydrophobic coating was completely frozen after 394 s, while this superhydrophobic coating can melt a 2 mm thick ice layer within 115 s under a voltage of 20 V. [93] Wang et al showed that superhydrophobic graphene composite can suppress ice nucleation of a water droplet (5 µL at −15 °C) for 335 s, and this superhydrophobic composite can melt an ice layer (≈3 mm) in 70 s under a voltage of 50 V because of the synergistic effect of surface superhydrophobicity and electro-thermal property. [91] Zhang et al designed a thermo-mechanical anti-icing/de-icing ) adapted with permission.…”
Section: Electro-thermal Promoted Aimmentioning
confidence: 99%
“…prepared a stretchable superhydrophobic coating (i.e., maintain superhydrophobicity under 300% strain) by embedding modified graphene into the Ecoflex elastomer to achieve the electrothermal ability for anti‐icing application. [ 93 ] A water droplet (5 µL at −15 °C) on this graphene‐based superhydrophobic coating was completely frozen after 394 s, while this superhydrophobic coating can melt a 2 mm thick ice layer within 115 s under a voltage of 20 V. [ 93 ] Wang et al. showed that superhydrophobic graphene composite can suppress ice nucleation of a water droplet (5 µL at −15 °C) for 335 s, and this superhydrophobic composite can melt an ice layer (≈3 mm) in 70 s under a voltage of 50 V because of the synergistic effect of surface superhydrophobicity and electro‐thermal property.…”
Section: Electro‐thermal Promoted Aimmentioning
confidence: 99%
“…Moreover, the heating effect can extend the longevity of the superhydrophobic coating by reducing the amount of degradation caused by repeated freezing and thawing action [6]. Heating the surface also mitigates frost formation, allowing superhydrophobic coatings to remain effective at shedding water at lower temperatures.…”
Section: Research Objectivesmentioning
confidence: 99%
“…In recent years, several other researchers have developed novel hybrid superhydrophobicelectrothermal coatings with unique materials, methods, and properties [6,7,8]. Many of these studies have focused on application to non-conductive glass, polymer, and composite substrates.…”
Section: Research Objectivesmentioning
confidence: 99%
See 1 more Smart Citation